2009
DOI: 10.1111/j.1365-2222.2009.03300.x
|View full text |Cite
|
Sign up to set email alerts
|

Toluene diisocyanate enhances human bronchial epithelial cells' permeability partly through the vascular endothelial growth factor pathway

Abstract: TDI increases the permeability of HBE cell monolayers, partly through a VEGF-mediated pathway. This suggests the importance of VEGF in TDI-induced pulmonary diseases, but shows that other pathways may be involved in the pathogenic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…Blocking VEGF signaling with VEGFR inhibitors reduced AHR and inflammation induced by TDI in a murine model . And we found increased expression of VEGF induced by TDI–HSA conjugate in our previous study . These studies suggest that VEGF is one of the major determinants of TDI‐induced asthma.…”
Section: Discussionsupporting
confidence: 90%
“…Blocking VEGF signaling with VEGFR inhibitors reduced AHR and inflammation induced by TDI in a murine model . And we found increased expression of VEGF induced by TDI–HSA conjugate in our previous study . These studies suggest that VEGF is one of the major determinants of TDI‐induced asthma.…”
Section: Discussionsupporting
confidence: 90%
“…Airway epithelia in asthmatics, especially in severe disease, exhibited disruption of tight junctions and increased permeability, while the mechanisms of this epithelial barrier dysfunction remain unclear. Zhao et al . reported that toluene diisocyanate, a well‐recognized chemical asthmogen, significantly increased the permeability of human bronchial epithelial cell monolayer.…”
Section: Basic Science Researchmentioning
confidence: 99%
“…Airway epithelia in asthmatics, especially in severe disease, exhibited disruption of tight junctions and increased permeability, while the mechanisms of this epithelial barrier dysfunction remain unclear. Zhao et al 51 reported that toluene diisocyanate, a well-recognized chemical asthmogen, significantly increased the permeability of human bronchial epithelial cell monolayer. This epithelial dysfunction was associated with a marked release of vascular endothelial growth factor, and vascular endothelial growth factor-neutralizing antibody could significantly lower the permeability.…”
Section: Mechanisms Related To Airway Epithelial Function and Damagementioning
confidence: 99%
“…The mechanism of sensitization is controversial because specific IgE antibodies against isocyanates are found in a minority of subjects with asthma. Isocyanates may directly damage airway epithelium through a GSH-dependent mechanism [32] and increase the permeability of bronchial epithelium through a VEGF-mediated pathway in vitro [33]. Occupational exposure to isocyanates enhances spontaneous IL-10 production by peripheral blood mononuclear cells (PBMC) [34].…”
Section: Occupational Asthmamentioning
confidence: 99%